Pengaruh Karakteristik Individu Terhadap Kinerja Auditor - Ceacilia Sri Mindarti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This study aims to analyze the influence of individual characteristics of auditors in terms of locus of control and organizational commitment to the performance of auditors. The theories that be used in this study are attribution theory and goal setting theory. Auditors in a public accounting firm in Indonesia with a minimum term of one year are selected as samples in this study. The research data were collected by questionnaires, which were processed using regression analysis. The results showed that individual characteristics which are locus of control and organizational commitment were influenced the performance of auditors. The results will contribute to the development of the auditing literature, especially regarding to the influence of individual characteristics on the auditor’s performance as well as performance of auditors.